Survival in Cystic Neoplasms of the Pancreas - Ali Cadili; Amy Bazzerelli; Sipi Garg; Robert Bailey (Canadian Journal of Gastroenterology)
BACKGROUND: The natural history of pancreatic cystic neoplasms remains poorly understood despite growing evidence on the subject. Pancreatic cysts display a wide spectrum of pathological phenotypes, each associated with a different prognostic implication. Many pancreatic cysts are of undetermined malignant potential at presentation and remain so until surgically resected. While the survival rates of patients with malignant cysts are known to be poor, survival rates in patients with undetermined pancreatic cysts are unknown.